VP30 Research And Analysis Of European Health Technology Assessment Processes. (2017) - Sus, Julia; Garrett, Zoe
Abstract : INTRODUCTION: As part of the European Network for Health Technology Assessment (EUnetHTA) Joint Action 3, the National Institute for Health and Care Excellence (NICE) in collaboration with forty-nine Health Technology Assessment (HTA) agencies and payer organizations, is leading on research to gain a high level understanding of HTA processes across Europe. This will help to facilitate improved collaboration and use of EUnetHTA HTA reports and tools across member states and decrease the duplication of work. To analyze the similarities and differences in HTA processes and decision making on the reimbursement of pharmaceuticals and medical devices across Europe. METHODS: National agencies involved in the HTA and reimbursement processes shared data on HTA and decision-making processes. Data provided was extracted into an excel workbook including information relating to pharmaceuticals, medical devices, inpatient and outpatient care and assessments that inform reimbursement, pricing and other processes. RESULTS: Thirty-one countries provided fifty-eight sets of HTA process and procedural documents for both medical devices and pharmaceuticals. This information was translated into the workbook which consisted of eleven sections (general information, capacity, overview of the process, topic selection, assessment process, advice and decision making, legal and procedural issues, reassessment, stakeholders engagement, HTA information used and HTA information held). The first stage of data analysis is a descriptive write up of existing processes from horizon scanning and topic selection up to decision making. The second stage is an analysis showing how collaboration and use of EUnetHTA outputs can be implemented into existing processes. An additional questionnaire will be developed to gain further understanding of EUnetHTA partners views on national engagement in the EUnetHTA procedures, implications of joint production, what EUnetHTA products are most valued and what mechanism might support better information sharing and more efficient use of HTA reports between jurisdictions. CONCLUSIONS: The analysis of the above data will provide detailed information on how EUnetHTA products or HTA products from other jurisdictions could be introduced into HTA and reimbursement processes across member states and at what point could EUnetHTA partners best engage in joint and cooperative work.